Interfaz de receptor de bucle de 4-20ma en aplicación con dspic - Valdivieso A., Carlos (2009)
This project was implemented with the aim of showing the benefits of using dsPIC applications in a long distance communication and develop a physical and functional software with LabVIEW. In this case we use the dsPIC to control the temperature required for the production of enzymes in the process of mashing malt. The loop receiver receives the signal from a temperature sensor in the form of voltage, which is conditioned and amplified before being transmitted as current over a long distance, in order to avoid interference from parasitic signals. The current receiver has an output of 0-5 VDC conditioned that connects to an analog input dsPIC30F4011 microcontroller to read the sensor data. This project will use LabVIEW to monitor the sensor signal through the VISA port driver and the dsPIC UART module. In addition the MAX232 integrated circuit is responsible for converting TTL signals to RS232 level signals that the computer reads.